How to Understand Customer Needs? The Role of Market Orientation, Innovation Capability, and Learning Orientation - M Sandi Marta; Ratih Hurriyati; Puspo Dewi Dirgantari (UIN Raden Mas Said Surakarta, 2021)
Excellent marketing is always oriented to the needs and desires of consumers, and consumer orientation is inseparable from a market orientation that the company must develop. This study aims to analyze the relationship between market orientation and customer loyalty with innovation capability as a mediator and learning orientation as a moderator in the relationship between innovation capability and customer loyalty. Data were collected using a cross-sectional survey among 95 online shop owners. Furthermore, the data were analyzed using Hayes' PROCESS macro-based hierarchical regression. The results revealed that market orientation had a positive effect on innovation capability. Innovation capability mediated the correlation between market orientation and customer loyalty. Furthermore, learning orientation reinforces the correlation between innovation capability and customer loyalty. These findings contribute to understanding the effect of innovation capability and learning orientation on market orientation and online shop customer loyalty.